Building Africa’s Homegrown Humanitarian Systems: Restoration as an Alternative to Localization - Boateng, Oheneba A. (Frontiers in Political Science, 2021)
Many humanitarian actors now recognize that it is crucial to build response structures on the basis of the norms, knowledge, and institutions of those affected by disasters. Currently, this concept has been captured through the term localization. However, the use of localization both as a term and process have so far been done without critical reflection on the traditional meaning of the term, and the impact of its historical application. It has also come about without proper historicization of the broader localization process and how this related to historical antecedents. This paper problematizes localization as a troubled term that describes a concept that has been applied in the past to help erode the homegrown humanitarian initiatives that Africans started. It draws attention to how international humanitarian actors established themselves in Africa as a process of localization which eventually contributed to the erosion of the homegrown initiatives that they interacted with. Given its historically erosive effects on homegrown initiatives, localization, the paper argues, is a troubled term that cannot be redeemed or repurposed for the current attempt to build humanitarian action on homegrown structures. A more reflective and appropriate term is restoration, which not only recognises this history of erosion, but repairs historical mistakes, and ensures that homegrown structures are built in a sustainable manner that avoids a repeat of those mistakes. Restoration in practice should be based on self-determination, and will depend on the leadership of African states, their ability to create a conducive environment for homegrown NGOs to thrive, and the successful synergies they build with other restoration processes across the continent. International actors will have to intentionally reconcile themselves with their erosion footprints, exercise restraint, and scale back their involvement so that local actors can gain the space to evolve. The paper concludes that all this starts with the ability of those leading the process to build homegrown structures to imagine an alternative humanitarian future.